Kidney transplantation, bioengineering, and regeneration kidney transplantation in the regenerative medicine era (Academic Press, 2017)
Kidney Transplantation, Bioengineering, and Regeneration: Kidney Transplantation in the Regenerative Medicine Era investigates how the field of regenerative medicine is changing the traditional premises of solid organ transplantation, specifically within the field of kidney transplantation. In Section 1, chapters illustrate the state of the art in kidney transplantation as well as the research behind the bioengineering and regeneration of kidney organoids for therapeutic renal replacement. In Section II, chapters catalog the technologies that are being developed and the methods that are being implemented to bioengineer or regenerate kidneys in order to restore function, while critically highlighting those technological advances which hold the most promise. The book thus encompasses clinical renal transplantation, tissue engineering, biomaterial sciences, stem cell biology, and developmental biology, as they are all applied to the kidney